Microencapsulation of Lactococcus lactis Gh 1 with gum arabic and Synsepalum dulcificum via spray drying for potential inclusion in functional yogurt - Fazilah, Nurul Farhana; Hamidon, Nurmelissa Hanani; Ariff, Arbakariya; Khayat, Mohd Ezuan; Wasoh @ Mohamad Isa, Helmi; Halim, Murni (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
There has been an explosion of probiotic incorporated based product. However, many reports indicated that most of the probiotics have failed to survive in high quantity, which has limited their effectiveness in most functional foods. Thus, to overcome this problem, microencapsulation is considered to be a promising process. In this study, Lactococcus lactis Gh1 was encapsulated via spray-drying with gum Arabic together with Synsepalum dulcificum or commonly known as miracle fruit. It was observed that after spray-drying, high viability (~10⁸ CFU/mL) powders containing L. lactis in combination with S. dulcificum were developed, which was then formulated into yogurt. The tolerance of encapsulated bacterial cells in simulated gastric juice at pH 1.5 was tested in an in-vitro model and the result showed that after 2 h, cell viability remained high at 1.11 × 10⁶ CFU/mL. Incubation of encapsulated cells in the presence of 0.6% (w/v) bile salts showed it was able to survive (~10⁴ CFU/mL) after 2 h. Microencapsulated L. lactis retained a higher viability, at ~10⁷ CFU/mL, when incorporated into yogurt compared to non-microencapsulated cells ~10⁵ CFU/mL. The fortification of microencapsulated and non-microencapsulated L. lactis in yogurts influenced the viable cell counts of yogurt starter cultures, Lactobacillus delbrueckii subs. bulgaricus and Streptococcus thermophilus.